2004
DOI: 10.1196/annals.1309.004
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Unique Population of CD8+ T Cells by Intestinal Epithelial Cells

Abstract: Intestinal epithelial cells may play a role in the regulation of immune responses toward luminal antigens. We show that a subset of CD8(+) T cells undergoes oligoclonal expansion in the intestinal mucosa, probably through interaction with a unique complex expressed on epithelial cells, formed by a CEA subfamily member (gp180) and CD1d. This subset, which is regulatory in vitro, may play a role in the control of intestinal immune responses toward luminal antigens. A lack of expansion of these CD8(+) regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Diverse reports have emphasized the key role of the IECs in promoting CD8 þ suppressor T cells. 2,3,37,38 In this work, we have furthered these observations and demonstrated that IECs can elicit effector and regulatory T-cell responses. We have shown that loss of Notch-1 induces increased intestinal permeability, dampens proinflammatory signals, and leads to inappropriate T-cell function.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Diverse reports have emphasized the key role of the IECs in promoting CD8 þ suppressor T cells. 2,3,37,38 In this work, we have furthered these observations and demonstrated that IECs can elicit effector and regulatory T-cell responses. We have shown that loss of Notch-1 induces increased intestinal permeability, dampens proinflammatory signals, and leads to inappropriate T-cell function.…”
Section: Discussionsupporting
confidence: 57%
“…1 The potential of IECs to promote regulatory T cells suggests a key role of IECs and the lymphoepithelial crosstalk in the maintenance of intestinal immune homeostasis. 2,3 This crosstalk is often disrupted, as seen in patients with food allergy, inflammatory bowel disease, celiac disease, and colonic cancer, 4 where alterations in cytokine secretion and regulatory T-cell function promote, rather than inhibit, inflammation. Further understanding of the nature of IEC/T-cell interactions during homeostasis will help decipher the mechanisms underlying the immune defects observed in disease states.…”
Section: Introductionmentioning
confidence: 98%
“…Previous work provides increasing evidence for an active role of intestinal epithelial cells (IECs) in sampling luminal antigens and modulating related immune responses as nonprofessional antigen presenting cells (APCs). Critically dependent on inflammatory influences, antigen presentation by IECs to CD4 ϩ and CD8 ϩ T cells might result in either regulatory or proinflammatory processes (1,4,18,38,41).Antigen-specific stimulation of CD4 ϩ and CD8 ϩ T cells requires T cell receptor interaction with major histocompatibility complex (MHC)-antigen complexes (9, 40). Presentation of exogenous antigens has classically been attributed to MHC II molecules and CD4 ϩ T cells.…”
mentioning
confidence: 99%
“…In the intestine, two major lymphocyte populations exist: the intraepithelial lymphocytes (IEL) which remain associated with the basolateral membrane of the IECs, and the LPL which localize to the subepithelial lamina propria and are in contact with IECs via basolateral projections through the semi-porous basement membrane 1,2 . Previous studies from our lab suggested that IECs function as antigen-presenting cells (APCs) and, as such, can promote regulatory T-cell responses in the mucosa [3][4][5][6][7][8] . In a reverse interaction, studies by Chen et al suggested that IEL could induce IEC differentiation via the production of keratinocyte growth factor (KGF) 9 .…”
Section: Introductionmentioning
confidence: 99%